Generation Y Behavior: Employee Loyalty Based on Job Satisfaction and Workplace Spirituality - Rohimat Nurhasan; Suwatno Suwatno; Eeng Ahman; Edi Suryadi; Rahyuniati Setiawan (Journal of International Conference Proceedings (JICP), 2021)
The present study is motivated by the belief that employee loyalty is an important factor that helps companies to survive in an increasingly fierce business competition. To generate employees’ loyalty, good workplace spirituality and job satisfaction are very much required. The aim of this study is to analyze the loyalty of Generation Y employees as the effect of job satisfaction and work spirituality at private universities in Garut Regency, Indonesia. To this end, the study utilized a descriptive and verification approach in which the data were collected from 132 respondents using the interviews, questionnaires and surveys. The respondents were chosen by using saturated or census sampling techniques. Then, the collected data were analyzed by using path analysis with SPSS 24.0 software. The results showed that of all the analyzed research variables, the criteria were quite high. Work spirituality and job satisfaction showed a significant effect on employee loyalty. The findings also indicated that the employees who feel the spiritual values at the workplace tend to stay in the organization. In addition, a fair and decent remuneration system makes the Generation Y employees feel satisfied.